人工膝関節全置換術の術前後における膝関節屈曲時の膝蓋下脂肪体の動態変化について: 超音波測定装置を用いて - 井尻, 朋人; 野際, 誉也; 愛須, 亮汰; 鈴木, 俊明; 大山, 明夏; 川﨑, 友祐希 (関西理学療法, 2023)
In this study, we measured the dynamics of the infrapatellar fat pad (IFP) associated with knee joint flexionin the postoperative period after total knee arthroplasty (TKA) using ultrasonography over the preoperative topostoperative period. We then investigated at what time point the dynamic decline of the IFP began to occur.The results suggest that the dynamics of the IFP had already decreased at one month postoperatively. Theresults also suggest that for postoperative TKA patients, intervention for the subpatellar fat body should beperformed within the first postoperative month, when the dynamic decline of the IFP begins to occur.